THE CORE MYTH OF PSYCHOANALYSIS: ON THE CENTENARY OF FREUD’S “TOTEM AND TABOO” - R. F. Dodeltsev; V. I. Konnov (Vestnik MGIMO-Universiteta)
The article attempts to evaluate the influence of one of the main works of S. Freud on the psychoanalysis of culture “Totem and Taboo”. The authors offer an overview of the history of the book’s creation including its psychoanalytical, anthropological and historical sources, analyze its main concepts among them the connection between ancient prohibitions and limitations imposed by neurotics on themselves, similarity between neurotic behavior and behavior of primitive people, examine the place of the book among other works by Freud such as “Mass psychology and Ego analysis”, “Cultural sexual morality and modern neurosis” and others. The article also investigates the main criticisms against Freud’s work launched from historical and psychological positions and tries to single out its constructive elements. The authors trace the reception of the book by literary circles, among others by T. Mann, who suggested viewing “Totem and Taboo” rather as a new kind of myth creation than a work of science. And then the article turns to attempts to apply the book’s ideas to the analysis of such events of modern history as the denazification of Germany and student uprising in the late 1960s following the works of the psychoanalyst M. Erdheim and philosopher O. Marquard. The authors conclude the article by offering their view of the possible applications of Freud’s concepts in the analysis of social processes, which could be based on combining the scientific approach favored by Freud himself, despite his leanings toward speculative theory, with methods of reflection typical for art, which build upon free associations of events and are directed towards the wide public rather than a narrow group of specialists.